Contract Theory - Bolton, Patrick (Massachusetts Institute of Technology, 2005)
Despite the vast research literature on topics relating to contract theory, only a few of the field's core ideas are covered in microeconomics textbooks. This long-awaited book fills the need for a comprehensive textbook on contract theory suitable for use at the graduate and advanced undergraduate levels. It covers the areas of agency theory, information economics, and organization theory, highlighting common themes and methodologies and presenting the main ideas in an accessible way. It also presents many applications in all areas of economics, especially labor economics, industrial organization, and corporate finance. The book emphasizes applications rather than general theorems while providing self-contained, intuitive treatment of the simple models analyzed. In this way, it can also serve as a reference for researchers interested in building contract-theoretic models in applied contexts.